A scent of lemon-seller meets buyer with a noisy quality observation - Mark Voorneveld; Jörgen W. Weibull (Games, 2011)
We consider a market for lemons in which the seller is a monopolistic price setter and the buyer receives a private noisy signal of the product's quality. We model this as a game and analyze perfect Bayesian equilibrium prices, trading probabilities and gains of trade. In particular, we vary the buyer's signal precision, from being completely uninformative, as in standard models of lemons markets, to being perfectly informative. We show that high quality units are sold with positive probability even in the limit of uninformative signals, and we identify some discontinuities in the equilibrium predictions at the boundaries of completely uninformative and completely informative signals, respectively.
Keywords: 330; lemons; adverse selection; noisy quality signals; two-sided incomplete information